DEVELOPED LIQUID FILMS FALLING AROUND TAYLOR BUBBLES INSIDE VERTICAL STAGNANT COLUMNS (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The present work reports an experimental study of developed liquid films falling around single Taylor bubbles inside vertical tubes containing stagnant liquids. Experiments were carried out in acrylic tubes with 2.0 m length and inner diameters of 0.019, 0.024 and 0.034 m. Five water-glycerin mixtures were used, corresponding to film Reynolds number（Ref）ranging from 2 to 7650. A pulse-echo ultrasonic technique was applied to measure the rise velocity of the bubble and the equilibrium thickness of the liquid film. These parameters together with the calculated standard deviation of the equilibrium film thickness provided information about the development of waves on the gas-liquid interfaces, which could be related with the laminar-turbulent transition of liquid films falling around Taylor bubbles. The results indicated that the wave amplitudes increased sharply for Ref> 1000. This value of Ref is in agreement with literature concerning the laminar-turbulent transition for free falling films on vertical surfaces.